2011
DOI: 10.5152/akd.2011.085
|View full text |Cite
|
Sign up to set email alerts
|

The comparison a 16-year follow-up results of balloon angioplasty for aortic coarctation in children of different age groups: a single-center experience

Abstract: Aort koarktasyonu tanısıyla balon anjiyoplasti uygulanan farklı yaş gruplarındaki çocukların 16 yıllık izlem sonuçlarının karşılaştırılması: Tek merkez deneyimiThe comparison a 16-year follow-up results of balloon angioplasty for aortic coarctation in children of different age groups: a single-center experience ABSTRACTObjective: Pediatric patients with different age groups who underwent balloon angioplasty for aortic coarctation were evaluated for recoarctation, aneurysm, peripheral arterial injuries and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It could be as high 3.7-7.7% and associated cardiac pathologies might increase mortality (12,13). Ergul et al (14) showed that isthmus hypoplasia and pulmonary hypertension were risk factors for AoC dilatation during neonatal period. The newborns, especially premature babies, undergoing balloon dilatation of AoC were at high risk for mortality (15).…”
Section: Discussionmentioning
confidence: 99%
“…It could be as high 3.7-7.7% and associated cardiac pathologies might increase mortality (12,13). Ergul et al (14) showed that isthmus hypoplasia and pulmonary hypertension were risk factors for AoC dilatation during neonatal period. The newborns, especially premature babies, undergoing balloon dilatation of AoC were at high risk for mortality (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is more frequent in boys, with a male/female ratio reported as being between 1:27 and 1:74. [6][7][8][9][10] It generally corresponds to the juxtaductal and discrete types, with long-segment and tortuous stenosis seen much less frequently. The transverse aortic arch and isthmus may be hypoplastic in the presence of a left ventricular outflow obstruction or left ventricular septal defect.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon dilatation is proposed in these patients with palliative intent so as to buy time in the presence of a poor general physical condition, concomitant left ventricular dysfunction, and/or complex cardiac lesions when emergency surgical repair cannot be performed. [7] The problems related to balloon angioplasty in neonates and young infants are varied and include the residual pressure gradient in the presence of longsegment coarctation or isthmic hypoplasia and the development of recoarctation or aneurysms. These problems are more frequent after dilatation than surgical repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that a hybrid technique can also be performed on carefully selected CoA and VSD patients to decrease the incidence of the complications noted above and to improve the prognosis. Considering the high possibility of recurrence of CoA with balloon angioplasty (9), patients with shortsegment (≤5 mm) CoA may be more suitable for balloon angioplasty. Therefore, in this study, we investigated the efficacy of combined balloon angioplasty and surgical repair for cases of short-segment CoA with VSD and compared outcomes with those of patients who received traditional surgical treatment.…”
Section: Original Articlementioning
confidence: 99%